2017
DOI: 10.18632/oncotarget.16385
|View full text |Cite
|
Sign up to set email alerts
|

Identification of KANSARL as the first cancer predisposition fusion gene specific to the population of European ancestry origin

Abstract: Gene fusion is one of the hallmarks of cancer. Recent advances in RNA-seq of cancer transcriptomes have facilitated the discovery of fusion transcripts. In this study, we report identification of a surprisingly large number of fusion transcripts, including six KANSARL (KANSL1-ARL17A) transcripts that resulted from the fusion between the KANSL1 and ARL17A genes using a RNA splicingcode model. Five of these six KANSARL fusion transcripts are novel. By systematic analysis of RNA-seq data of glioblastoma, prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 52 publications
1
42
0
Order By: Relevance
“…However, this assumption is certainly improbable. This is firstly because it would require an inversion of the genomic structure to place the ARL17A gene downstream KANSL1 , and additionally by the existence of multiple KANSL1-ARIL1A isoforms 13 . Therefore, it is reasonable to think that this fusion results from two steps: first an inversion and subsequently a fusion event between a 5′breakpoint downstream of the KANSL1 exon 3 and a 3′ breakpoint occurring upstream of the ARL17A exon 3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, this assumption is certainly improbable. This is firstly because it would require an inversion of the genomic structure to place the ARL17A gene downstream KANSL1 , and additionally by the existence of multiple KANSL1-ARIL1A isoforms 13 . Therefore, it is reasonable to think that this fusion results from two steps: first an inversion and subsequently a fusion event between a 5′breakpoint downstream of the KANSL1 exon 3 and a 3′ breakpoint occurring upstream of the ARL17A exon 3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another notable fusion is the previously reported cancer predisposition KANSARL fusion between KANSL1 and ARL17A genes on chromosome 17q21.31; however, in similar proportions in SWNTS-SWNs and NS-SWNs (Online Resource Fig. 4) [45].…”
Section: Transcriptome Profile Of Swnts-swnsmentioning
confidence: 61%
“…Among NSL complex members driving cancer traits, mutations in KANSL1 have been reported to promote malignancies. Zhou and co‐workers recently identified a KANSL1‐ARL17A fusion transcript in cancer samples isolated specifically from patients with European ancestry . KANSL1 and ARL17A are neighboring genes on human chromosome 17.…”
Section: Nsl Complex In Human Health and Diseasementioning
confidence: 99%
“…KANSL1 and ARL17A are neighboring genes on human chromosome 17. The authors found that the KANSL1‐ARL17A fusion is inherited within European populations and could predispose carriers to cancer . In addition, KAT6B‐KANSL1 translocations have been identified in a woman with retroperitoneal leiomyoma , but how the KAT6B‐KANSL1 translocation drives this cancer remains to be identified.…”
Section: Nsl Complex In Human Health and Diseasementioning
confidence: 99%